Wind tunnel testing of the aerodynamic and ballistic characteristics of the aircraft anti-armor bomb - Novaković, Zoran Đ. (Vojnotehnički glasnik / Military Technical Courier, 2015)
Wind tunnel testing of an aircraft anti–armor bomb (PTAB) is performed to determine its aerodynamic coefficients at subsonic and transonic flow regimes. In the same regimes, the fuze mechanism arming time is tested, directly depending on the local flow field around the anti-armor bomb. The objective of this investigation is to define a reliable method of determining the fuze mechanism arming time. A verification of the same characteristics of the anti–armor bomb in real flight conditions will be taken into consideration to approve the method after wind tunnel testing. Introduction Growing efficiency of air defense systems imposes on attacking aircraft to perform attacks at low altitude (at as low altitude as possible) and to leave the target area as fast as possible. This, in turn, imposes additional demands on aircraft weapons (bombs) which have to be slowed on their ballistic path with remote/temporal armed fuzes in order to avoid endangering aircraft by accidental bomb explosion on its ballistic path or bomb explosion on the target. Wind tunnel testing of anti-armor bombs precedes flight testing in order to approve designed ballistic characteristics and fuze arming time or to make some potential corrections on all samples of anti-armor bombs of a nationally produced prototype lot, before expensive flight testing. Preceding bomb ballistic paths calculations that include the designed aerodynamic coefficients and the adopted aircraft low level flight minimum altitude - Hmin with a speed bombing range of va=(650÷1100)km/h for the given type of aircraft show a mutual position of the aircraft and the anti-armor bomb (Fig. 1.). The impulse rejecting mechanism deliver to the bomb the orthogonal starting velocity vyo to the horizontal airstream (aircraft velocity va). The bomb sweeps out from the container into the horizontal airstream which causes the rotation of the fuze arming mechanism vane, while body tail fins are deployed instantly to stabilize and slow the bomb along its ballistic path. The fuze arming time measured from the instant when the pilot triggers the button is acceptable within the interval (t1, t2). The time t1 is determined by the criteria of the critical distance lkr, from the aircraft to the bomb (Savezni sekretarijat za..., 1988.) at the instant of fuze arming). The time t2 is determined from the condition of timely fuze arming, i. e. before the bomb impacts the target. The anti-armor bomb fuze is a percussion type of the fuze with initial chain interruption, remote-temporal arming and self destruction. The fuze arming time is a cumulative time of a defined chain of events (aircraft electrical installation relays the execution time-T1, impulse rejecting mechanism the execution time-T2, fuze arming mechanism the execution time-T3, fuze firing pin above percussion primer relocation the execution time -T4). The T1, T2, and T4 times are in miliseconds, while T3 is in seconds. Since there is a significant difference in time orders of magnitude, it could be adopted t ≈ T3. The wind tunnel test model geometric and aerodynamic characteristics are similar to the original object. Also, the model is modified for two kinds of wind tunnel testing: 1. Tensiometric sting-balance measuring of aerodynamic forces and moments of the test bomb model configuration without the arming vane mechanism, (Fig. 3), 2. T3 - time determination: The arming mechanism vane number of revolutions measured from the instant of the vane unlock (a moment when the wind tunnel achieves the desired Mach number) to the instant of the vane separation from the tail stabilizer tail unit, (Fig. 4). Both tests are performed with characteristic Mach numbers: 0.6, 0.7, 0.8, and 0.9, which covers the interval of aircraft motion speed (180÷310) m/s, (Etkin,1964). Test Model Description The anti-armor bomb model with its own aerodynamic and geometric characteristics corresponds to the original, in scale 1:1. The bomb model is modified to be integrated with the ABLE MK XXV 1 sting-balance (Anastasijević, et al, 2001.). The anti-armor bomb body is of a cylindrical shape with a front flat surface. The bomb tail unit comprises six radial folding fins located peripherally (Fig. 2), and the arming vane mechanism on the back side. Four centrifugal safety pins radially located on the arming vane peripheral side are pulled out (at the critical number of revolutions when the arming vane is separated) to enable the initial chain set up i.e. fuze arming. Testing Description and Data Processing The measuring of aerodynamic forces and moments as well as the arming mechanism execution time-T3 was performed in the Trisonic Wind Tunnel T-38 MTI SA. Aerodynamic forces and moments were measured on the ABLE tensiometric six-component sting-balance on a straight sting, (Fig. 3) without test model base drag correction (Samardžić, et al, 2014.). In addition to the axial force component of the sting-balance, other characteristics (vertical force component, lateral force, pitching moment, yawing moment, rolling moment) were measured, which was not a requirement of the test. All characteristics are presented in a form of aerodynamic coefficients as a function of the angle of attack, Table 1 and Table 2. Measuring ballistic functional caracteristics (T3, n) was performed on a broken sting (Fig. 4) with a set-up angle of 15°. Both experiments were perfomed in the transonic working sector of the wind tunnel T-38 wind tunnel, with airflow speeds corresponding to Mach numbers from 0.6 to 0.9. Data collecting was accomplished by the TELEDYNE acquisition sistem. Data processing was performed using the APS data processing software package. The tubule is installed onto the bomb body in order to verify the arming vane number of revolutions and the arming vane separation time (T3). Its one end is located close to the rotating arming vane over which top four reefs of centrifugal safety pins are run. The tubule records the reefs run over (rotation of the arming vane) as a frequency of the air pressure changing, and records the instant of the arming vane separation as an abrupt change of an average pressure amount by means of a differential pressure transducer (PRT) installed into the bomb body (Fig. 5). Since the expected arming vane number of revolutions is 3000 r.p.m., the transducer signal is filtered by a 1000Hz digital filter. At a wind tunnel airflow speed of 200 m/s, with the equivalent Mach number of M=0.6, the dominant frequency f=190 Hz is obtained. Taking into consideration the number of arming vane reefs N=4, the number of arming vane revolutions is obtained: n=2850 min-1 Test Results The sting-balance measurements showed an unexpectedly large drag coefficient (Cx=4.41, Table 1), due to the deployed stabilizer fins. The role of stabilizer fins is to slow down the bomb (to decrease its speed and stabilize it on its balistic path), and to retard it with relation to the aircraft. In order to confirm the drag influence of stabilizer fins, measurements were repeated with the blunt body configuration after folding fins subassembly dismantling the folding fins subassembly. The result was the expected drag coefficient (Cx=0.79, Table 2) as the referent wind tunnels achieved world-wide, (Hoerner, 1965), (Finck, 1978). The measured time of approximately 10s did not correspond to the expected arming mechanism reaction time for two reasons: 1. Airflow acceleration to the desired Mach number in the wind tunnel, i.e. arming vane rotation during this time does not correspond to the real usage of the anti-armor bomb. The arming mechanism vane falls into the aircraft speed horizontal airflow (the desired Mach number in the wind tunnel) instantly in the real flight conditions. 2. Arming vane mechanism design characteristic does not permit multiple usage, which could not be avoided in testing because one and the same mechanism was used many times. For these reasons, the bomb test model and the experiment were redesigned. A sufficient number of samples of the arming mechanism vane were provided for each individual wind tunnel blowing. The bomb model redesign was perfomed in a way to prevent the arming mechanism vane from rotating until the blow pressure and the Mach number achieve desired values in the wind tunnel. Since the bomb body was discharged, the interior bomb body room was used to accommodate electro magnets I and II, (Fig. 6) which lock/unlock the arming mechanism vane by its lifter (6) and locking fork (7) . Electro magnet I locks the arming vane mechanism durring airflow acceleration in the wind tunnel. At the instant of a wind tunnel airflow desired Mach number, Electro magnet I releases the locking fork while Electro magnet II pulls the locking fork back in order to unlock the arming vane mechanism. The arming mechanism vane starts to rotate at a desired Mach number (aircraft speed) which corresponds to real conditions of the anti-armor bomb usage. Conclusion New wind tunnel tests with a redesigned bomb test model are upcoming after providing an adequate number of arming mechanism vanes. The objective of these wind tunnel tests is obtaining a curve of the arming mechanism vane number of revolutions depending on the surrounding flow speed around the redesigned bomb test model. If the results of wind tunnel tests (with the redesigned bomb test model) are confirmed with the results of flight testing (with an actual anti-armor bomb), this wind tunnel testing could be accepted as a reliable method of fuze arming mechanism time determination of this kind of a bomb fuze. This wind tunnel testing will replace the expensive flight testing.